2018
DOI: 10.3892/ol.2018.9151
|View full text |Cite
|
Sign up to set email alerts
|

18F‑FDG PET/CT for the early prediction of the response rate and survival of patients with recurrent or metastatic breast cancer

Abstract: The present study aimed to explore the value of fludeoxyglucose F 18 positron emission tomography-computed tomography (PET/CT) for the early prediction of chemotherapy remission rates and survival in patients with recurrent and metastatic breast cancer. A total of 24 patients diagnosed with recurrent or metastatic breast cancer between 2009 and 2014 were enrolled. All patients underwent a PET/CT examination prior to (PET/CT1) and following (PET/CT2) chemotherapy. Differences of PET/CT1 maximal standardized upt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…These patterns are in line with the findings of our study to some degree and could be explained by the inability of CE-CT to distinguish osteoblastic bone lesions from bone healing. They also showed that FDG-PET/CT could be a better predictor for progression-free survival and disease-specific survival compared to CE-CT [17], which was proposed in some other studies as well [24,25]. These results indicate that FDG-PET/CT may be superior to CE-CT in the response assessment of MBC patients [17,24,25].…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…These patterns are in line with the findings of our study to some degree and could be explained by the inability of CE-CT to distinguish osteoblastic bone lesions from bone healing. They also showed that FDG-PET/CT could be a better predictor for progression-free survival and disease-specific survival compared to CE-CT [17], which was proposed in some other studies as well [24,25]. These results indicate that FDG-PET/CT may be superior to CE-CT in the response assessment of MBC patients [17,24,25].…”
Section: Discussionmentioning
confidence: 73%
“…They also showed that FDG-PET/CT could be a better predictor for progression-free survival and disease-specific survival compared to CE-CT [17], which was proposed in some other studies as well [24,25]. These results indicate that FDG-PET/CT may be superior to CE-CT in the response assessment of MBC patients [17,24,25].…”
Section: Discussionmentioning
confidence: 73%
“…14 Diagnosis of pleural metastasis is essential considering that the most common pleural malignancy is the metastatic involvement in which high incidence causative primary diseases are bronchogenic carcinoma, breast carcinoma and lymphoma. 15,16 PET/CT scan is an efficient imaging method for initial staging, assessment of treatment response and evaluation of recurrence by quantitating FDG avidity of cancer with standardized uptake value. Limited by low sensitivity to detect breast cancers smaller than 1 cm and lobular carcinomas, PET/CT still has efficacy superior to convential imaging for the locoregional spread and distant metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Limited by low sensitivity to detect breast cancers smaller than 1 cm and lobular carcinomas, PET/CT still has efficacy superior to convential imaging for the locoregional spread and distant metastasis. [15][16][17][18] Moreover, PET/CT is considered to be more valuable in diagnosing skeletal metastasis compared with bone scintigraphy and predicting recurrence. [18][19][20][21][22][23][24] This study distinctly states that absence of FDG uptake in pleura or pleural effusion minimizes the risk of metastasis regarding that none of 15 patients with no avidity in PET/CT were diagnosed with a pleural malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in tumor metabolic activity, assessed by [ 18 F]F-FDG PET/CT, are an early indicator of treatment effectiveness for breast cancer, in both neoadjuvant and metastatic settings [ 5 ]. Likewise, a significant reduction in the metabolic activity of the tumor (i.e., treatment-sensible tumors), early during therapy, is associated with longer overall survival and progression-free survival in this tumor [ 6 ]. However, in metastatic disease, the post-therapeutic response assessment frequently shows heterogeneous responses, which means that responding and nonresponding metastatic lesions coexist (dissociated response) [ 7 ].…”
Section: Introductionmentioning
confidence: 99%